The Influence of Minimum Competency Assessment, Character Survey, and Learning Environment Survey on the Quality of Islamic Junior High School Athirah Bone. - Syarifuddin, Samsinar S (DIDAKTIKA, 2024)
This study discusses the Effect of Minimum Competency Assessment, Character Survey, and Learning Environment Survey on the Quality of Islamic Junior High School Athirah Bone. This research is a field research and this type of research is quantitative with a descriptive approach. The population in this study were all students at Islamic Junior High School Athirah Bone which amounted to 201 people, thus, the number of samples in this study was 45 people. The techniques used in data collection by means of questionnaires and documentation. The results showed that there was a significant effect simultaneously (together) between the minimum competency assessment, character survey, and learning environment survey on the quality of Islamic Junior High School Athirah Bone. The average minimum competency assessment is 28.16 with a standard deviation of 5.966, the average character survey is 70.24 with a standard deviation of 8.781, and the average learning environment survey is 46.27 with a standard deviation of 6.051.Â